District Competition in Japan's 2014 Election: The Roles of Nominations, Incumbency, and Dual Listing. Issue 2 (2nd July 2016) - Rich, Timothy S.; Banerjee, Vasabjit
Abstract : Duverger's Law expects two-party competition in single member districts (SMDs), but evidence from mixed member systems is less consistent with these theoretical expectations. Rather than simply focusing on whether Japan's most recent House of Representatives election converges toward Duvergerian equilibrium, this article focuses on three factors within Japan. In particular, how do the roles of major party nominations, incumbency, and dual-listing shape district competition vis-à-vis Duverger? Empirical results find that the lack of a Democratic Party of Japan candidate decreases the effective number of candidates, while the lack of a Liberal Democratic Party candidate, multiple incumbents, and dual-listing correlates with an increased number of candidates. The results suggest that often ignored underlying effects of Japan's mixed system influences its consistency with theoretical expectations.